PENINGKATAN KAPASITAS UMKM MELALUI PELATIHAN DIGITAL MARKETING BERBASIS MEDIA SOSIAL DESA SUKAMULYA KABUPATEN CIANJUR - Qadaar, Amiruddin; Sariputri, Sariputri; Wahyuni, Wahyuni; Sinta Sariputri, Sinta Sariputri; Sri Wahyuni, Sri Wahyuni (ICON Publisher, 2025)
This community service program aims to improve digital literacy and marketing skills of MSME actors in Sukamulya Village, Cianjur Regency, through social media-based digital marketing training. This activity was carried out from January to February 2025, with interactive training methods, direct practice, and intensive mentoring. The results of the activity showed a significant increase in participants' understanding and skills in creating promotional content, managing social media accounts, and utilizing marketplace platforms. The formation of a digital MSME community and increased online transactions are indicators of the success of this program. The village government expressed support for the continuation of the program and is committed to providing village fund allocations. The conclusion of this activity shows that digital marketing training contributes to local economic transformation, increasing the competitiveness of small businesses, and establishing a digital business ecosystem at the village level. This activity can be replicated in other villages with a local needs-based approach, multi-sector collaboration, and adequate infrastructure support.